Communication In Islamic Educational Institutions - Nurhasnah, Nurhasnah; Amanur Latifah; Ridhatul Husna; Tiwi Putria Yosnela (International Journal of Education, Vocational and Social Science, 2022)
The purpose of this paper is to find out that communication in Islamic education plays an important role with a literature and literature approach that is relevant to the research topic. The results of the analysis that the authors get from the communication are vital in the implementation of Islamic educational institutions. The success of Islamic educational institutions is influenced by many factors including the management and communication that each stakeholder has in carrying out their responsibilities. So it is clear that there is a significant relationship between communication and the Islamic educational institution itself.